2017
DOI: 10.3390/su9112142
|View full text |Cite
|
Sign up to set email alerts
|

On the Sustainability of Co-Authoring Behaviors in Vietnamese Social Sciences: A Preliminary Analysis of Network Data

Abstract: Abstract:The topic of sustainability has mostly been tied to economic development and environmental protection, yet not much attention has been paid to the need for high problem-solving capacity as this underlines both issues. One of the most straightforward ways to improve problem-solving capacity is to nurture 'productive and enduring', i.e., sustainable, scientific communities. The study examines the co-authoring behaviors of 412 Vietnamese social scientists over the 2008-2017 period via social network anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…These questions give rise to the need for understanding the upcoming acculturation process both within academia and beyond [39,40]. In the Vietnamese context alone, Ho et al found the possibility of a research network to be socially unsustainable due to the big gap between the most productive researcher and the remaining members of his or her network [44]. This kind of study allows local researchers to grasp their own academic landscape, thereby improving their collaboration, as well as helping to inform policy-makers.…”
Section: Discussionmentioning
confidence: 99%
“…These questions give rise to the need for understanding the upcoming acculturation process both within academia and beyond [39,40]. In the Vietnamese context alone, Ho et al found the possibility of a research network to be socially unsustainable due to the big gap between the most productive researcher and the remaining members of his or her network [44]. This kind of study allows local researchers to grasp their own academic landscape, thereby improving their collaboration, as well as helping to inform policy-makers.…”
Section: Discussionmentioning
confidence: 99%
“…Vuong and his associates are among the most active in this field. Using data extracted from the Scopus database in conjunction with data from local sources such as university websites, this research team has produced a series of publications (e.g., see [3,[29][30][31][32][33] ) about the research outputs of Vietnamese social scientists and related factors.…”
Section: Previous Studies On Factors Impacting International Publishingmentioning
confidence: 99%
“…The second part of the survey included 13 five-point Likert scale items pertaining to 13 factors affecting international publishing (see Table 3). These items were developed based on previous studies relating to our topic, including Pham and Hayden [34]; Chang and Chow [24]; Li [25]; Vuong et al [3]; Ho et al [29]; Pho and Tran [4]; Vuong and Tran [32]. The third part of the survey was composed of two open-ended questions.…”
Section: Roundmentioning
confidence: 99%
“…On a smaller scale, one such project of data gathering and storage was the Network of Vietnamese Scientists in Social Sciences and Humanities Project (https://sshpa.com). The result is rather significant: data extracted from this project had been utilized in seven publications (see Ho et al, 2017a;Ho et al, 2017b;Ho et al, 2017c;Vuong et al, 2017;Vuong et al, 2018c;Vuong et al, 2019c;Vuong et al, 2018a).…”
Section: Recommendationsmentioning
confidence: 99%